Sovietų režimo santykis su naminio alaus gamyba ir pardavinėjimu Šiaurės Lietuvoje XX a. penktajame–šeštajame dešimtmečiais - Indrišionis, Darius (Genocidas ir rezistencija, 2024)
This research focuses on Soviet politics towards home-made beer brewing and selling in postwar Lithuania. After Soviet occupation of Lithuania along with other domestic economical activities, home-made beer brewing became illegal in Lithuanian SSR: due to Soviet Criminal Code, illegal brewers could be sent to a hard labour camp up to 2 years and if there were some elements of speculation (for example, if grains for home-made beer brewing were bought from other people in local marketplace), home-made brewers could be imprisoned up to 10 years. From 1948 to 1955 in Soviet Lithuania there were at least 46 cases of home-made beer brewers sentenced by Soviet Lithuania`s courts. After 1953, this process became less harsh – more often an alternative ways of punishment were used.